2000
DOI: 10.1038/sj.onc.1203504
|View full text |Cite
|
Sign up to set email alerts
|

Haploid loss of the tumor suppressor Smad4/Dpc4 initiates gastric polyposis and cancer in mice

Abstract: The tumor suppressor SMAD4, also known as DPC4, deleted in pancreatic cancer, is a central mediator of TGF-b signaling. It was previously shown that mice homozygous for a null mutation of Smad4 (Smad4 7/7 ) died prior to gastrulation displaying impaired extraembryonic membrane formation and endoderm dierentiation. Here we show that Smad4 +/7 mice began to develop polyposis in the fundus and antrum when they were over 6 ± 12 months old, and in the duodenum and cecum in older animals at a lower frequency. With i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
160
0
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(171 citation statements)
references
References 45 publications
8
160
0
3
Order By: Relevance
“…In about 10-20% of colorectal tumors, DPC4 undergoes mutation (Hadzija et al, 2004). Also, it has been shown that Smad4 þ /À heterozygous mice develop inflammatory gastric polyps and tumors at about 12 months of age, with loss of the wild-type Smad4 allele (Xu et al, 2000). These tumors show moderate stromal cell proliferation, infiltration by eosinophils and plasma cells, as well as foci of adenocarcinoma with signet ring cells.…”
Section: Introductionmentioning
confidence: 99%
“…In about 10-20% of colorectal tumors, DPC4 undergoes mutation (Hadzija et al, 2004). Also, it has been shown that Smad4 þ /À heterozygous mice develop inflammatory gastric polyps and tumors at about 12 months of age, with loss of the wild-type Smad4 allele (Xu et al, 2000). These tumors show moderate stromal cell proliferation, infiltration by eosinophils and plasma cells, as well as foci of adenocarcinoma with signet ring cells.…”
Section: Introductionmentioning
confidence: 99%
“…It was recently reported that loss of one copy of a gene without any alteration in the remaining wild-type allele, a phenomenon referred to as haploinsufficiency, may be sufficient to promote cancer in many instances. Such is the case with the PTEN gene in solid renal cell carcinomas (Velickovic et al, 2002), SMAD4 in gastric cancers (Xu et al, 2000;Maurice et al, 2001) and p27 in various other cancers (Fero et al, 1998;Philipp-Staheli et al, 2001). Our data raise the possibility that haploinsufficiency of PTC may be involved in early UC, at least in tumours with LOH of the PTC marker.…”
mentioning
confidence: 81%
“…Using the Cre-loxP-mediated tissue specific knockout approach to overcome embryonic lethality, we showed that mice lacking Smad4 in their mammary glands displayed abnormal differentiation of mammary epithelium and tumorigenesis (Li et al, 2003b). Meanwhile, Smad4 heterozygous mice developed gastric polyposis and cancer (Redman et al, 2005;Takaku et al, 1999;Xu et al, 2000), and one out of 16 Smad4 þ /À mice also developed squamous cell carcinomas (SCCs) of the skin (Redman et al, 2005), suggesting that Smad4 also functions as a tumor suppressor in the mouse.…”
Section: Introductionmentioning
confidence: 99%